THE ROLE OF VOLATILES IN THE THERMAL HISTORY OF METAMORPHIC TERRANES - Brady John B. (My University, 1988)
Analytical and numerical solutions to the differential equations for the conduction of heat with heat production or with fluid flow have been used to evaluate the role of volatiles in the thermal history of regional metamorphic terranes. The maximum thermal effect from pervasive, single-pass, regional volatile flow may be predicted from a steady-state solution given by Bredehoeft and Papadopoulos (1965). For fluid velocity vF (m/s) and connected porosity ?, combinations of volatile flux vF (m3 of fluid/m2s) and transport distance L(m) such that vL is greater than 3?6?10?7 should produce regional temperature increases due to fluid flow, if the flow persists for l05–106 a (depending on the transport distance L). The absolute value of the temperature increase due to volatile flow will be greater in regions with higher ambient geothermal gradients. For L=20 km, a volatile flux of 1?8 ? 10?11 (m3 of fluid/m2s) or greater is required to achieve a temperature effect. Few geologic processes release volatiles at this rate for extended periods of time, so regional thermal effects from the single-pass, pervasive flow of volatiles are unlikely. A new analytical solution for the steady state temperature distribution between idealized parallel channels of fluid flow is presented along with the results of two-dimensional numerical models of channelized fluid flow. Both approaches show that little temperature increase is expected near channels of fluid flow relative to the rocks between the channels, unless the channels exceed 100 m in width or unless the fluid fluxes are very large and transient. A possible thermal effect of volatile flow in metamorphic terranes is the production of metamorphic hot spots due to focusing of volatiles into widely spaced channels or conduits exceeding 1 km in width. Given a sufficient fluid flux (exceeding 10?10 m3 of fluid/m2s), thermal gradients of over 100K from center to edge may be produced in such channels during relatively short time intervals (105–106a).